One-step synthesis of graphene via catalyst-free gas-phase hydrocarbon detonation - Nepal, Arjun; Singh, Gajendra P.; Flanders, Bret N.; Sorensen, Christopher M. (My University, 2013)
A one-step, gas-phase, catalyst-free detonation of hydrocarbon (C[subscript 2]H[subscript 2]) method was developed to produce gram quantities of pristine graphene nanosheets (GNs). The detonation of C[subscript 2]H[subscript 2] was carried out in the presence of O[subscript 2]. The molar ratios of O[subscript 2]/C[subscript 2]H[subscript 2] were 0.4, 0.5, 0.6, 0.7, and 0.8. The obtained GNs were analyzed by XRD, TEM, XPS and Raman spectroscopy. The GNs are crystalline with (002) peak centered at 26.05° (d = 0.341 nm). TEM shows that the GNs are stacked in two to three layers and sometimes single layers. An increase in the size of GNs (35-250 nm) along with reduction in defects (Raman I[subscript D]/I[subscript G]~ 1.33- 0.28) and specific surface area (187 to 23 m²gˉ¹) was found with increasing O[subscript 2] content. The high temperature of the detonation, ca. 4000K, is proposed as the cause of graphene production rather than normal soot. The method allows for the control of the number of layers, shape and size of the graphene nanosheets. The process can be scaled up for industrial production.
Keywords: Condensed matter; Surfaces; Chemical physics; Physical chemistry